Winning the discursive struggle? The impact of a significant environmental crisis event on dominant climate discourses on Twitter. (March 2022) - Bednarek, Monika; Ross, Andrew S.; Boichak, Olga; Doran, Y.J.; Carr, Georgia; Altmann, Eduardo G.; Alexander, Tristram J.
Abstract: The devastating 2019–2020 Australian bushfires attracted significant activity on social media, both in Australia and worldwide. We use corpus-based discourse analysis to explore the impact of this significant environmental crisis event on climate discussions on Australian Twitter, with a focus on discursive struggle and (de-)legitimation. We examine the most-retweeted tweets across three 30-day time periods, combining quantitative and qualitative approaches. Methodologically, we analyse hashtags to identify dominant Twitter discourses in the three phases. We also explore tweets that support or oppose the link between climate change and the fires, and the misleading arson discourse. We use collocation and concordance analysis, developing a new approach to categorising tweets for support and opposition. Results show that the bushfires had a clear impact on dominant Twitter climate discourses, that this intensified at the height of the bushfires, but receded significantly afterwards. Additionally, climate disinformation discourses seem to be a 'minor' dominant discourse rather than a 'major' dominant discourse in the Twitter datasets under investigation. Our study suggests that discursive legitimation becomes an outcome of discursive struggle; the very act of retweeting a tweet suggesting the bushfire crisis is indicative of the urgent need for broad climate action is, in a sense, contributing to the legitimisation of this discourse and countering the arguments of those who do not see the issues as linked.